Mixed Cu(II)-Bi(III) metal organic framework with a 2D inorganic subnetwork and its catalytic activity - Shi, Fa-Nian
The very dense (d = 4.359 g cm(-3)) three dimensional (3D) hybrid heterometallic framework Bi3O2Cu(OH)(pdc)(2) (pdc(3-):3,5-pyrazoledicarboxylate), 1, features a 2D inorganic subnetwork representing an unprecedented topological type, and is an effective catalyst for the diastereoselective synthesis of E-alpha,beta-unsaturated ketones.